Application of MEAD method for occupational disease risk control in hotel housekeeping department - Saputra , Manggala Rasendriya; Lucitasari, Dyah Rachmawati; Al-Bana , Nuzila Putri (OPSI, 2025)
Housekeeping activities in the hospitality industry are essential for service quality but are frequently associated with occupational health risks that may reduce productivity and increase employee health problems. Most existing prevention efforts focus on task-level hazards, with limited consideration of organizational and macro-level factors. Therefore, this study applies the Macroergonomic Analysis and Design (MEAD) method to address occupational disease risks in a hotel housekeeping department. Four major risk factors were identified: environmental exposure to chemical odors and waste; equipment and facility limitations, including restricted trolley mobility and inadequate Personal Protective Equipment (PPE); worker-related health complaints, reported by 67% of workers for skin and respiratory symptoms and by 50% for eye irritation, abrasions, and skin redness, with overlapping symptoms; and organizational factors related to insufficient operational supervision. Using the ten-stage MEAD framework, the housekeeping work system was redesigned through administrative controls, PPE provision, and safety awareness interventions. Post-implementation evaluation using Job Safety Analysis (JSA) showed a clear reduction in health complaints, with respiratory and skin irritation decreasing from frequent to rare and eye irritation and abrasions declining from occasional to non-occurring. These results demonstrate that MEAD is an effective framework for improving occupational health and safety in hotel housekeeping operations.